Siap Menyusui, Siap Memberi Yang Terbaik: Edukasi Persiapan Fisik dan Mental Bagi Calon Ibu dan Ibu Menyusui di Kota Depok - Destrikasari, Charisma; Aprillia, Yuna Trisuci; Rahmadhanny, Ratih (Jurnal Pelayanan dan Pengabdian Masyarakat (Pamas), 2026)
Breast milk (ASI) is the best source of nutrition for infants to support optimal growth and immunity. However, exclusive breastfeeding coverage in Indonesia remains below the national target of 80%. This community service activity by the Indonesian Breastfeeding Mothers Association (AIMI) Depok Chapter aimed to improve mothers’ physical and mental readiness through practical breastfeeding education and interactive discussions. The activity was held on January 11, 2025, at Sukmajaya Public Health Center, Depok, involving 11 pregnant participants in their second and third trimesters. Evaluation was conducted using a satisfaction questionnaire completed by 50% of participants. Results showed that all aspects of the activity were rated good to very good, with an average score of 4.64 out of 5. The highest score was achieved in the prenatal yoga session (5.0), followed by the speaker’s delivery, topic relevance, and breastfeeding materials (4.6–4.8). Methods and media, venue comfort, refreshments, and overall implementation were also rated very good (4.6), while punctuality received a slightly lower score (4.4). All respondents found the materials interesting, relevant, and easy to understand, and noted that the speaker delivered them clearly and communicatively. Participants reported that simulation practices helped them understand correct latching and positioning, while yoga and group discussions enhanced their calmness and confidence. This activity demonstrates that practice-based education combined with lactation counselor support and light physical exercise, such as yoga, effectively increases maternal readiness and confidence for breastfeeding. Further continuous programs and follow-up evaluations are recommended to assess long-term impact on exclusive breastfeeding success